THE INFLUENCE OF THE AGRICULTURAL INDUSTRY CHAIN ON REGIONAL SPECIAL AGRICULTURAL PRODUCTS A STUDY ON THE MODERATION ROLE OF THE GOVERNMENT FROM THE PERSPECTIVE OF AGRICULTURAL RESOURCE AREAS - Gong, Fayong (Journal of Buddhist Education and Research (JBER), 2023)
Engage in agricultural planting, agricultural products or agronomic processing in the northeastern region, Inner Mongolia and areas along the Great Wall, the Huanghuaihai region, the Loess Plateau region, the northwest arid region, the plain hilly region in the middle and lower reaches of the Yangtze River, the hilly and mountainous region in the south of the Yangtze River, the southeast region, the southwest region and the Qinghai-Tibet Plateau region With the samples of food processing professionals, the questionnaire survey method was used to investigate the various dimensions of agricultural industry chain optimization, government support and the actual situation of the competitiveness of regional agricultural products. The moderating role of government support in the relationship between the optimization of the agricultural industry chain and the competitiveness of regional characteristic agricultural products is tested. The data is analyzed by SPSS26 and Mplus8.3 software, and it is concluded that the regions where the growth area conditions have a significant impact on the characteristic agricultural products are: the Huanghuaihai region, the northwest arid region and the Qinghai-Tibet Plateau region; the current situation of the agricultural industry has a great influence on the competitiveness of the characteristic agricultural products. Significantly affected areas are: Northeast China, Huanghuaihai District, Northwest arid area, Jiangnan hilly area, and southwest area; areas where processing industry status has a significant impact on the competitiveness of characteristic agricultural products are: Inner Mongolia and areas along the Great Wall, Northwest arid area, Jiangnan Hilly area, southwest area; the areas where infrastructure conditions have a significant impact on the competitiveness of characteristic agricultural products are: northeast area, northwest arid area; in all 10 areas, the level of marketing management cannot significantly affect the competitiveness of characteristic agricultural products. The moderating effect of government support also shows regional differences. The regions where government support has a moderating effect on the competitiveness of characteristic agricultural products by the growing regional conditions include: Northeast China, Inner Mongolia and the regions along the Great Wall, the middle and lower reaches of the Yangtze River, the hilly region of the south of the Yangtze River, the southeast region, and the Qinghai-Tibet Plateau. The areas where government support has a moderating effect in the impact of the current situation of the agricultural industry on the competitiveness of characteristic agricultural products are: Northeast China, Loess Plateau, Jiangnan Hilly, Southeast, and Southwest. The areas where government support has a moderating effect on the status quo of the processing industry affecting the competitiveness of characteristic agricultural products are: Inner Mongolia and areas along the Great Wall. Government support does not play a moderating role in the influence of infrastructure conditions and marketing management level on the competitiveness of characteristic agricultural products in any region. The research conclusions of this paper will play a very important role in the optimization of the agricultural industry chain, the formulation of agricultural support policies by the government, and the enhancement of the competitiveness of characteristic agricultural products by enterprises.